Bid-Induced Release of AIF/EndoG from Mitochondria Causes Apoptosis of Macrophages during Infection with Leptospira interrogans - Wei-Lin Hu (Frontiers in Cellular and Infection Microbiology, 2017)
Leptospirosis is a global zoonotic infectious disease caused by pathogenic Leptospira species. Leptospire-induced macrophage apoptosis through the Fas/FasL-caspase-8/3 pathway plays an important role in the survival and proliferation of the pathogen in hosts. Although, the release of mitochondrial apoptosis-inducing factor (AIF) and endonuclease G (EndoG) in leptospire-infected macrophages has been described, the mechanisms linking caspase and mitochondrion-related host-cell apoptosis has not been determined. Here, we demonstrated that leptospire-infection induced apoptosis through mitochondrial damages in macrophages. Apoptosis was caused by the mitochondrial release and nuclear translocation of AIF and/or EndoG, leading to nuclear DNA fragmentation. However, the mitochondrion-related CytC-caspase-9/3 pathway was not activated. Next, we found that the release and translocation of AIF and/or EndoG was preceded by the activation of the BH3-interacting domain death agonist (Bid). Furthermore, our data demonstrated that caspase-8 was activated during the infection and caused the activation of Bid. Meanwhile, high reactive oxygen species (ROS) trigged by the infection caused the dephosphorylation of Akt, which also activated Bid. In conclusion, Bid-mediated mitochondrial release of AIF and/or EndoG followed by nuclear translocation is a major mechanism of leptospire- induced apoptosis in macrophages, and this process is modulated by both caspase-8 and ROS-Akt signal pathways.